Expert PHP and MySQL - Curioso, Andrew; Bradford, Ronald; Galbraith, Patrick; Safari Technical Books (Indianapolis, IN : Wiley Pub., 2010)
Looks at the techniques of creating applications using PHP with MySQL, with information on such topics as design patterns, complex queries, iterators, closures, caching, PHP extensions, and Sphinx.
Looks at the techniques of creating applications using PHP with MySQL, with information on such topics as design patterns, complex queries, iterators, closures, caching, PHP extensions, and Sphinx.
Techniques every expert programmer needs to know -- Advanced PHP concepts -- MySQL drivers and storage engines -- Improving performance through caching -- Memcached and MySQL -- Advanced MySQL -- Extending MySQL with user-defined functions -- Writing PHP extensions -- Full-text searching -- Multi-tasking in PHP and MySQL -- Rewrite rules -- User authentication -- Understanding the INFORMATION_SCHEMA -- Security -- Command-line and web services -- Optimization and debugging.
"Wrox programmer to programmer"--Cover.
Includes index.
Keywords: MySQL (Electronic resource); PHP (Computer program language); Electronic books